PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, KEPUASAN, DAN LOYALITAS KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PADA KFC HASAN BASRI DI SAMARINDA - Vinna Desiana (University of Widya Gama Mahakam Samarinda, 2021)
This study aims to determine Product Quality, Service Quality, Satisfaction, and Consumer Loyalty to Purchase Decisions at KFC Hasan Basri in Samarinda. The number of samples is 100 respondents who are consumers of KFC Hasan Basri in Samarinda. Methods of data collection using a questionnaire. Determination of the sample size in this study is to use the Slovin formula. The data analysis method uses multiple linear regression with T test and F test to determine the joint and partial effect using the SPSS ver 23 program. (Y) while the variables of Service Quality (X2) and Satisfaction (X3) have no significant effect on Consumer Decisions (Y).